2016
DOI: 10.1016/j.chb.2015.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Control your Facebook: An analysis of online privacy literacy

Abstract: For an effective and responsible communication on social network sites (SNSs) users must decide between withholding and disclosing personal information. For this so-called privacy regulation, users need to have the respective skills-in other words, they need to have online privacy literacy. In this study, we discuss factors that potentially contribute to and result from online privacy literacy. In an online questionnaire with 630 Facebook users, we found that people who spend more time on Facebook and who have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 39 publications
3
106
1
2
Order By: Relevance
“…According to this view, many users simply lack understanding and awareness of online privacy risks (Bartsch & Dienlin, 2016;Hoofnagle, King, Li, & Turow, 2010;Trepte et al, 2015). Such a lack of understanding and awareness may be due to users' digital skills, or lack thereof (Dienlin & Trepte, 2015;Park, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this view, many users simply lack understanding and awareness of online privacy risks (Bartsch & Dienlin, 2016;Hoofnagle, King, Li, & Turow, 2010;Trepte et al, 2015). Such a lack of understanding and awareness may be due to users' digital skills, or lack thereof (Dienlin & Trepte, 2015;Park, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Thus, general Internet skills and, more specifically, privacy skills or literacy might be a better predictor of privacy behavior than privacy concerns. Yet, a recent study on privacy literacy (Bartsch & Dienlin, 2016) reveals that most users' privacy literacy is low (with little variance in privacy literacy) and that its effect on (social) privacy behavior is weak.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, given the small effect sizes, future studies might want to include measures of users' privacy literacy or privacy awareness (Park, 2013). Previous research has shown that higher levels of privacy literacy (Bartsch and Dienlin, 2016) or privacy awareness (Park, 2013) lead to a more controlled and safer use of social network sites, possibly limiting the harm and increasing the benefits.…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…An important reason why we focused on declarative knowledge as a predictor of privacy protective behavior concerns the potential circularity of the relationship between them. Indeed, recent research (Bartsch & Dienlin, 2016) provides reasons to call into question the direction of causality between previous experience in privacy protective behavior and procedural knowledge of how to do so. Still, analysis of the respective influence of declarative and procedural knowledge on privacy protective behavior would be valuable in future research, particularly if studied longitudinally or in controlled experiments that may help test this causal mechanism.…”
Section: Limitations and Future Researchmentioning
confidence: 99%